1999
DOI: 10.1046/j.1432-1327.1999.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial thioredoxin reductase in bovine adrenal cortex

Abstract: Mitochondrial thioredoxin reductase was purified from bovine adrenal cortex. The enzyme is a first protein component in the mitochondrial thioredoxin-dependent peroxide reductase system. The purified reductase exhibited an apparent molecular mass of 56 kDa on SDS/PAGE, whereas the native protein was about 100 kDa, suggesting a homodimeric structure. It catalysed NADPH-dependent reduction of 5,5 H dithiobis(2-nitrobenzoic acid) and thioredoxins from various origins but not glutathione, oxidized dithiothreitol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…All TrxR from mammalian cells, of which there are a growing number of isoenzymes (19,(31)(32)(33), have the conserved C-terminal sequence -Gly-Cys-SeCys-Gly and a subunit with homology to GR (10) including the identical conserved active site of the latter enzyme (19,(31)(32)(33). However, the detailed mechanism of mammalian TrxR has not been known.…”
Section: Discussionmentioning
confidence: 99%
“…All TrxR from mammalian cells, of which there are a growing number of isoenzymes (19,(31)(32)(33), have the conserved C-terminal sequence -Gly-Cys-SeCys-Gly and a subunit with homology to GR (10) including the identical conserved active site of the latter enzyme (19,(31)(32)(33). However, the detailed mechanism of mammalian TrxR has not been known.…”
Section: Discussionmentioning
confidence: 99%
“…By reduction of hydroperoxides to the corresponding alcohols, these enzymes can prevent the production of reactive oxygen radicals and thus may contribute to the protection of the Selenium in Biology 851 Ursini et al, 1982;Brigelius-Flohé et al, 1994 Plasma GPx (pGPx, GPx-3) Takahashi et al, 1987 Gastrointestinal GPx (GI-GPx, GPx-GI, GPx-2) Chu et al, 1993 Iodothyronine deiodinases 5Ј-deiodinase, type I (5ЈDI) Behne et al, 1990;Arthur et al, 1990 5Ј-deiodinase Lee et al, 1999;Watabe et al, 1999;Miranda-Vizuete et al, 1999;Gasdaska et al, 1999 Thioredoxin reductase homologs (SelZf1; SelZf2) Lescure et al, 1999 Selenophosphate synthetase-2 Guimaraes et al, 1996 Functionally undefined 15 kDa selenoprotein of T cells Gladyshev et al, 1998 Selenoprotein P 10 (SelP) Motsenbocker and Tappel organism's macromolecules and biomembranes against oxidation (Sies et al, 1972;Flohé, 1989;Ursini et al, 1995). The role of the cytoplasmic GPx as an 'emergency enzyme' to fight oxidative stress was verified by reverse genetics (Ho et al, 1997;Cheng et al, 1998;de Haan et al, 1998;Fu et al, 1999;Jaeschke et al, 1999) and, in this role, cGPx cannot be substituted by any of the other selenoproteins.…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
“…It needs selenocysteine as the penultimate amino acid residue for its appropriate enzymatic function (Marcocci et al, 1997;Gromer et al, 1998;Lee et al, 2000;Gorlatov and Stadtman, 2000). Recently, two more tissue-specifically expressed isoenzymes were also identified as selenoproteins (Gasdaska et al, 1999;Lee et al, 1999;Watabe et al, 1999) and related proteins were identified by 'in silico' cloning (Lescure et al, 1999). Various natural and synthetic compounds, apart from disulfide groups in peptides and proteins, can be reduced by TrxR Björnstedt et al, 1995).…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
“…Disruption of the gene for thioredoxin 1, a 12-kDa thiol disulfide oxidoreductase, results in embryonic lethality in mice (4) demonstrating an essential role of the thioredoxin system in the development of mammals. Three distinct thioredoxin reductases (TRs) 1 (5)(6)(7)(8)(9)(10) are responsible for maintaining thioredoxins in a reduced state and are also capable of reducing a great variety of other protein and nonprotein redox substrates. The cytosolic thioredoxin reductase (TR1), the most characterized of the three enzymes, was known for decades, but only recently it was found to be a selenium-containing protein (11).…”
mentioning
confidence: 99%
“…Recently, two additional thioredoxin reductases, TR2 and TR3, were identified that contained the conserved selenocysteine residue (5)(6)(7)(8)(9)(10). These enzymes had also other sequences essential for catalytic activity, including an N-terminal disulfide active center, NADPH-and FAD-binding domains and dimer interface sequences (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%